Q:

Simplify the expression 2(x + 7)(x2 − 3x − 6). 2x3 − 28x2 − 18x − 84 2x3 − 18x2 − 28x − 84 2x3 + 8x2 − 54x − 84 2x3 + 4x2 − 27x − 42

Accepted Solution

A:
Answer:The answer is C, 2x^3 + 8x^2 - 54x - 84. (I took a test and got this correct)Step-by-step explanation:Distribute the 2 to the numbers in parenthesis.The equation should now look like this.(2x + 14)(x^2 - 3x - 6)Multiply the right side by the left side, here are the results I got.2x * x^2 = 2x^32x * -3x = -6x^22x * -6 = -12x14 * x^2 = 14x^214 * -3x = -42x14 * -6 = -84.Now assemble the new equation.2x^3 - 6x^2 + 14x^2 - 42x - 12x - 84Now combine like terms.2x^3 - 8x^2 - 54x - 84Hope this helps you!